Foreign Language Learning Strategies in the Context of STEM Education - Han, Turgay (GIST – Education and Learning Research Journal, 2015)
This study aims at providing an insightful evaluation of the EFL strategies used by firstyear STEM (science, technology, engineering, and mathematics) students, and their perceptions of their own use of strategies. The 147 participants were undergraduate level, first-year engineering students at a state university in Turkey. Their ages ranged from 18 to 24. They took the Young Learners’ Language Strategy Use Survey (LSS). In addition, a sub-sample of students was interviewed about the strategies they used in learning language skills. The results showed that the students tended to employ various strategies in learning different language skills, but did not frequently use or practice these strategies. Further, vocabulary strategies and pronunciation skills were believed to be effective in conveying and deciphering meaning. These results suggest that language learning strategy training should be provided in STEM education.